Quantitative Sensory Testing of Spinal Cord and Dorsal Root Ganglion Stimulation in Chronic Pain Patients. Issue 4 (20th January 2021) - Sankarasubramanian, Vishwanath; Chiravuri, Srinivas; Mirzakhalili, Ehsan; Anaya, Carlos J.; Scott, John Ryan; Brummett, Chad M.; Clauw, Daniel J.; Patil, Parag G.; Harte, Steven E.; Lempka, Scott F.
Abstract: Background/Objectives: The physiological mechanisms underlying the pain‐modulatory effects of clinical neurostimulation therapies, such as spinal cord stimulation (SCS) and dorsal root ganglion stimulation (DRGS), are only partially understood. In this pilot prospective study, we used patient‐reported outcomes (PROs) and quantitative sensory testing (QST) to investigate the physiological effects and possible mechanisms of action of SCS and DRGS therapies. Materials and Methods: We tested 16 chronic pain patients selected for SCS and DRGS therapy, before and after treatment. PROs included pain intensity, pain‐related symptoms (e.g., pain interference, pain coping, sleep interference) and disability, and general health status. QST included assessments of vibration detection theshold (VDT), pressure pain threshold (PPT) and tolerance (PPToL), temporal summation (TS), and conditioned pain modulation (CPM), at the most painful site. Results: Following treatment, all participants reported significant improvements in PROs (e.g., reduced pain intensity [ p  < 0.001], pain‐related functional impairment [or pain interference] and disability [ p  = 0.001 for both]; better pain coping [ p  = 0.03], sleep [ p  = 0.002]), and overall health [ p  = 0.005]). QST showed a significant treatment‐induced increase in PPT ( p  = 0.002) and PPToL ( p  = 0.011), and a significant reduction in TS ( p  = 0.033) at the most painful site, but showed no effects on VDT and CPM. We detected possible associations between a few QST measures and a few PROs. Notably, higher TS was associated with increased pain interference scores at pre‐treatment ( r  = 0.772, p  = 0.009), and a reduction in TS was associated with the reduction in pain interference ( r  = 0.669, p  = 0.034) and pain disability ( r  = 0.690, p  = 0.027) scores with treatment. Conclusions: Our preliminary findings suggest significant clinical and therapeutic benefits associated with SCS and DRGS therapies, and the possible ability of these therapies to modulate pain processing within the central nervous system. Replication of our pilot findings in future, larger studies is necessary to characterize the physiological mechanisms of SCS and DRGS therapies.